Estrogen Plus Progestin Hormone Therapy and Ovarian Cancer: A Complicated Relationship Explored. Issue 3 (May 2020) - Lee, Alice W.; Wu, Anna H.; Wiensch, Ashley; Mukherjee, Bhramar; Terry, Kathryn L.; Harris, Holly R.; Carney, Michael E.; Jensen, Allan; Cramer, Daniel W.; Berchuck, Andrew; Doherty, Jennifer Anne; Modugno, Francesmary; et al.
Abstract : Background: Menopausal estrogen-alone therapy is a risk factor for endometrial and ovarian cancers. When a progestin is included with the estrogen daily (continuous estrogen–progestin combined therapy), there is no increased risk of endometrial cancer. However, the effect of continuous estrogen–progestin combined therapy on risk of ovarian cancer is less clear. Methods: We pooled primary data from five population-based case–control studies in the Ovarian Cancer Association Consortium, including 1509 postmenopausal ovarian cancer cases and 2295 postmenopausal controls. Information on previous menopausal hormonal therapy use, as well as ovarian cancer risk factors, was collected using in-person interviews. Logistic regression was used to assess the association between use of continuous estrogen–progestin combined therapy and risk of ovarian cancer by duration and recency of use and disease histotype. Results: Ever postmenopausal use of continuous estrogen–progestin combined therapy was not associated with increased risk of ovarian cancer overall (OR = 0.85, 95% CI = 0.72, 1.0). A decreased risk was observed for mucinous ovarian cancer (OR = 0.40, 95% CI = 0.18, 0.91). The other main ovarian cancer histotypes did not show an association (endometrioid: OR = 0.86, 95% CI = 0.57, 1.3, clear cell: OR = 0.68, 95% CI = 0.40, 1.2; serous: OR = 0.98, 95% CI = 0.80, 1.2). Conclusions: Given that estrogen-alone therapy has been shown to be associated with increased risk of ovarian cancer, these findings are consistent with the hypothesis that adding a progestin each day ameliorates the carcinogenic effects of estrogen on the cells of origin for all histotypes of ovarian cancer. Abstract : Supplemental Digital Content is available in the text.